Perspektif Sifat ‘Ajuula dalam Al-Qur’an Menurut Ibnu Katsir - Wisqa, Urwatul (ANWARUL, 2023)
Ajuula or what is commonly called haste. Haste is to look for something or choose it before the time comes according to lust, and this is usually based on lust. So there is the expression "the haste of the devil." Humans in a hurry are usually difficult to control their emotions and thoughts. In fact, usually their minds and hearts are empty. Often people are hasty or hasty in matters of worship. In this current era, we see that many people regret so much that their regrets are useless. It's a shame because they were in a hurry in dealing with a number of things that they should have been patient with first. This research uses library research, or library research, namely by collecting material related to the theme being researched. The method used is the Maudhu'i interpretation method. Therefore, the researcher concluded that it is forbidden to be hasty in doing things in life, therefore this hasty nature needs to be avoided by increasing worship of Allah, dhikr, getting used to deliberation, completing work in an orderly and effective manner, and recognizing one's limits.